Cuckoo Sandbox VS Virus Total: Categorical Analysis between Sandboxes: Categorical Analysis Between Sandboxes - Karthic Anna Ravi Maran; Nurul Azma Abdullah (Applied Information Technology And Computer Science, 2023)
This comparative study aims to assess the effectiveness of Cuckoo Sandbox and Virus Total in accurately identifying and categorizing malware samples as either threats or benign files, while optimizing overall performance. The research entails collecting malware samples, establishing the experimental environment, subjecting the files to analysis within the respective sandboxes, and evaluating the results based on specific measurements. These measurements include file scanning time, sandbox system utilization, and file identification accuracy. The findings provide compelling evidence supporting the superior performance of Virus Total, which achieved a perfect accuracy score of 1.0 while maintaining high efficiency. In contrast, limitations arising from the lack of up-to-date support in Cuckoo Sandbox hindered its performance. This research contributes to advancing the field of sandbox solutions by deepening our understanding of sandbox performance and offering insights for the development of more effective malware analysis tools.